Manajemen Pengembangan Kurikulum Madrasah Berbasis Ilmu Sosial Profetik dalam Mewujudkan Madrasah Unggul di MA An Nawawi Berjan Purworejo - Sulis Rokhmawanto; Dwi Marlina; Umi Arifah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Insitut Agama Islam Nahdlatul Ulama (IAINU) Kebumen, 2020)
This study aims to analyze the management of prophetic social science-based madrasah curriculum development in realizing superior madrasas at MA An Nawawi Berjan Purworejo. This study uses a qualitative case study approach with data collection techniques carried out through a process of observation, interviews, and documentation. Data analysis was carried out by recording data, data reduction, data display, data and drawing conclusions. The results of research in the implementation of prophetic social science-based curriculum management at MA An-Nawawi Berjan Purworejo that in the content of the material integrate general material with religious material as a foundation for transcendence values. In the application of the value of humanism, it has become a culture of pesantren where the interaction of hablun minannas is intertwined because pesantren and madrasah are places for social interaction between students with different backgrounds. The learning method used is the scientific method in the general learning process, while the integrated material uses the sorogan, bandongan, lecture, question and answer methods, practice with the content of the material being taught adjusted.